Сказки леса: литературно-художественное издание / В. В. Бианки, Н. И. Сладков - Бианки Виталий Валентинович (Родничок ; М. : Астрель, 2011)
Экземпляры: б/ф №10 () / Инвентарный номер: 35461 / Цена: 143.00 / Авт.знак: Б 59 / ГРНТИ: 17 / ББК: 84 (2Рос=Рус)6